Kesulitan Pembelajaran Matematika Sekolah Inklusi untuk Anak ABK - Chatarina Febriyanti; Mohamad Lutfi Nugraha (SAP (Susunan Artikel Pendidikan), 2017)
The research is aimed at knowing the difficulty with mathematics learning facing by students with special needs in an inclusive school. The research location chosen using a selected sampling technique is SDIT Akhdor Insan Mulia in Depok, West Java. The sample of the research is students with special needs with medium category and low category and students with special needs with slow learner category. The method of the research is an explorative survey with a qualitative approach. From the research result, it can be concluded that mathematics learning process for students with special needs requires a special treatment and a curriculum adjusted to the initial student?s ability so that students with special needs have a different mathematics curriculum than that of regular students.